(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The cultural heritage of Uzbekistan—comprising ancient cities, architectural masterpieces, and intangible traditions—plays a vital role in the country’s growing tourism industry. In recent decades, international relations have significantly contributed to the restoration and preservation of Uzbekistan’s cultural heritage through financial support, technical expertise, and collaborative projects. This paper explores how partnerships with global organizations such as UNESCO, the World Bank, and foreign governments have revitalized historic sites and improved tourism infrastructure. By fostering cross-border cooperation, Uzbekistan not only preserves its identity and cultural legacy but also strengthens its global image as a tourism destination.